2010
DOI: 10.1590/s1516-35982010000900028
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento ingestivo diurno de novilhos Nelore recebendo níveis crescentes de suplementação em pastejo de capim-braquiária

Abstract: RESUMO -Objetivou-se avaliar o comportamento ingestivo diurno de novilhos em pastagem de capim-braquiária submetidos a suplementação energética e proteica. Foram utilizados 40 novilhos Nelore, com peso inicial de 373,7 + 14,9 kg e 26 meses de idade, distribuídos em quatro níveis de suplementação: mistura mineral, 0,3; 0,6 e 0,9% do peso vivo de suplementação energética e proteica. Os animais foram observados visualmente por dois períodos de 12 horas; das 6 às 18 h. and because of the roughage:concentrate ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 19 publications
4
23
2
6
Order By: Relevance
“…Those results differ from the ones reported by Silva et al (2010), who fed heifers grazing Brachiaria brizantha cultivar Marandu with mineral salt and energy and protein supplementation at the levels of 3, 6 and 9 g/kg of body weight and found a reduction in NDF ingestion due to the observed replacement effect. Over grazing periods, NDF intake increased linearly (P<0.05) by 0.046 kg per day, following the tendency observed in the chemical analyses (Table 2), which presented an increase of 0.57 g/kg more dry matter in the NDF content as the experimental period advanced.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Those results differ from the ones reported by Silva et al (2010), who fed heifers grazing Brachiaria brizantha cultivar Marandu with mineral salt and energy and protein supplementation at the levels of 3, 6 and 9 g/kg of body weight and found a reduction in NDF ingestion due to the observed replacement effect. Over grazing periods, NDF intake increased linearly (P<0.05) by 0.046 kg per day, following the tendency observed in the chemical analyses (Table 2), which presented an increase of 0.57 g/kg more dry matter in the NDF content as the experimental period advanced.…”
Section: Resultscontrasting
confidence: 99%
“…It was found that even with the difference in grazing, the time of rumination did not change, and reduction in grazing time by supplementation with BRM and BRM + MEG increased the idle time of the animals. Silva et al (2010) found variations in grazing and idle activities as the supplementation level increased but with no alteration in rumination time. According to Moreno et al (2008), supplementation with corn meal at the level of 10 g/kg of the body weight for calves grazing year ryegrass decreased grazing time and increased idle time with no effect on rumination, probably in function of the existence of the supplement replacement effect by pasture.…”
Section: Resultsmentioning
confidence: 89%
“…The results for grazing time (494 min, on average), were lower than those found by Silva et al (2004), who evaluated the feeding behavior of ¾ Holstein × Zebu heifers on Brachiaria decumbens pasture with levels of supplementation in the trough and found grazing times varying between 10.35 and 11.03 h. The lower values found in the present study are due to the fact that animals remained in the waiting corral after milking, awaiting completion of the milking time for all animals.…”
Section: Resultscontrasting
confidence: 72%
“…Nevertheless, the disposal of males of dairy breeds is a practice that is not consistent with the moral and rational purposes that aim the welfare of animals and may thus tarnish the sustainable image and ethics of dairy farming. Several studies have sought techniques to improve the production of these animals (ALVES et al, 2004;SILVA et al, 2007;ZANINE et al, 2006). Based on this, it is concluded that among many factors influencing animal performance, as those related to diet, environmental and management differences, behavioral patterns, in general, serve as a basis to select the best feeding strategy of animals, whether in feedlot or pasture systems.…”
Section: Introductionmentioning
confidence: 99%